2006
DOI: 10.7547/0960132
|View full text |Cite
|
Sign up to set email alerts
|

The Physician’s Attire and Its Influence on Patient Confidence

Abstract: Although physician appearance has been a topic of discussion in the medical literature for many years, no objective research has been performed on this topic in the field of podiatric medicine. Our primary objective was to examine patient confidence in physicians as it relates to professional clinic attire versus casual or scrub outfits. We also assessed the influence of other variables, such as white coat, name tag, age, and sex, on patient confidence. We surveyed 155 podiatric medical patients from a private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 11 publications
4
39
0
1
Order By: Relevance
“…The findings of Ikusaka et al. (9) are in line with our study, reporting that patients disliked the white coat, and younger patients stated that it increases their emotional strain during the visit. In our study, parents repeatedly mentioned that the white coat is ‘old style’ and should be limited to ‘adult medicine’.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of Ikusaka et al. (9) are in line with our study, reporting that patients disliked the white coat, and younger patients stated that it increases their emotional strain during the visit. In our study, parents repeatedly mentioned that the white coat is ‘old style’ and should be limited to ‘adult medicine’.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, a number of parents expressed the importance of wearing a name tag. This is in line with other studies (9,10,12,13) and clearly demonstrates that – independently from the outfit – the paediatrician in the hospital should always wear such a tag.…”
Section: Discussionsupporting
confidence: 92%
“…However, other physical characteristics found to make patients uncomfortable in this previous human study were tattoos and male physicians wearing earrings (Budny et al . ) but this did not appear to negatively affect the majority of respondents. The reason for this disparity may reflect differences in perception or opinion of physicians compared to veterinarians or regional differences and attitudes towards certain aspects of outward appearance as well.…”
Section: Discussionmentioning
confidence: 84%
“…This is similar to a previous study in human medicine that identified facial piercings as the most common physical characteristic identified that caused patients to be less confident in their physician (Budny et al . ). However, other physical characteristics found to make patients uncomfortable in this previous human study were tattoos and male physicians wearing earrings (Budny et al .…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have analysed the effects of the physicians' white coats on patients compared with non-conventional attire such as, for example, informal 'everyday' clothing. In particular aspects that have been examined so far are the pathophysiological effects such as the 'white coat syndrome' (Pickering et al 1988) and the effects on the patients' trust and confidence in their physician (Matsui et al 1998, Menahem & Shvartzman 1998, Nair et al 2002, Cha et al 2004, Rehman et al 2005, Budny et al 2006. Little can be found in literature on the impact of nursing attire on patients and in particular, on paediatric patients.…”
Section: Introductionmentioning
confidence: 99%